Transformational leadership, innovative climate, and self-efficacy on teacher innovativeness: the mediating roles of digital literacy and achievement motivation - Vera Sri Wahyuni; Sri Setyaningsih; Lina Novita (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
Teacher innovativeness is critical for 21st-century education, yet the mechanisms linking organizational and psychological factors to innovative behavior remain underexplored, particularly the mediating roles of digital literacy and achievement motivation. This study examines the direct and indirect effects of transformational leadership, innovative climate, and self-efficacy on teacher innovativeness, mediated by digital literacy and achievement motivation. A quantitative survey was conducted with 232 public primary school teachers in Depok City, Indonesia, selected via multistage proportional random sampling (population N=3,664). Data were analyzed using path analysis and SITOREM (Scientific Identification Theory to Conduct Operation Research in Education Management). All five predictors had positive direct effects on teacher innovativeness (p<0.05). Achievement motivation was the strongest direct predictor (β = 0.385), followed by digital literacy (β= 0.297). Innovative climate was the strongest predictor of both digital literacy (β= 0.557) and achievement motivation (β= 0.451). Digital literacy and achievement motivation significantly mediated all indirect paths (Sobel test, p < 0.05). SITOREM identified priority indicators for improvement (e.g., implementation of innovation, risk tolerance, digital ethics). Teacher innovativeness is enhanced through a systemic approach addressing leadership, climate, self-efficacy, digital literacy, and motivation with achievement motivation and digital literacy serving as key mediating mechanisms. Schools should prioritize fostering innovative climate and strengthening achievement motivation through targeted professional development and recognition systems.